Ity Inclusive Learning Of Culinary Culinary Arts Based On Direct Practice To Develop The Creativity Of Pkbm Hspg Learners - Eva Hudiafa; Ahmad Rizaldi (Jurnal Pendidikan Tata Boga dan Teknologi, 2026)
This study aims to describe the implementation of inclusive learning based on direct practice in culinary classes and analyze its contribution to the development of learners' creativity at PKBM HSPG Serang City. The study employed a descriptive qualitative  approach  involving  eleven  informants  consisting  of  one  academic  coordinator,  two  culinary  instructors,  one parent/guardian,  and  seven  Package  A  learners.  Data  were  collected  through  in-depth  interviews,  participatory observation, and documentation studies. Data analysis followed the Miles and Huberman model, including data reduction, data display, and conclusion drawing. The findings indicate that direct practice-based learning enhances learners' creativity, independence, self-confidence, collaboration skills, and willingness to explore new ideas. These improvements were reflected in  learners'  ability  to  modify  food  presentation,  make  decisions  during  practical  activities,  interact  with  peers,  and confidently present their work. The results also reveal that direct practice provides concrete learning experiences that facilitate understanding  and  support  the  gradual  development  of  skills  according  to  each  learner's  abilities.  Therefore,  inclusive learning based on direct practice can serve as an effective strategy for fostering creativity and vocational skills development among learners in community learning centers.